WRF sensitivity to land use and urban canopy model during a heat wave event in Stockholm - Bernardo, Carolina Mateus Eiras (2020)
Heatwaves are among the most dangerous extreme weather events, and their occurrence is projected to significantly increase over Europe in a climate change scenario. Densely urbanized regions as cities, are more vulnerable to extreme hot weather events, than rural areas, due to pre-existing UHI effect. The present work evaluates the WRF model sensitivity to landuse and Urban Canopy Model (UCM) parametrizations, during a heat wave event occurring in Stockholm region. The landuse sensitivity test compares the model results produced with three different landuse datasets, showing that using a more updated and high-resolution dataset increases the model skill simulating wind and temperature fields. The UCM sensitivity, compared the model performance coupled with two UCMs, SLUCM and BEP model, using a high resolution landuse dataset with three different urban categories. The simulated results showed that these models are strongly dependent on the parameters used by each model to describe the city geometry and proprieties, besides this, using the BEP model increased the model skill simulating the u and v wind components, but the differences found for the temperature field were insignificant.